Keripik Rebung :Kreativitas Mahasiswa PGSD Sebagai Upaya Untuk Membentuk Jiwa Enterpreneur - Kurniawati, Wahyu; Rasyid, Said Agil AR; Kusuma, Panji Arya; Aisyah, Fatma Nur; Fadhilah, Arina Rochmah (Universitas Nusantara PGRI Kediri, 2022)
Bamboo shoots are young shoots or saplings that grow from bamboo roots. Bamboo shoots are also known as young bamboo. Bamboo shoots include vegetables that are liked by many people. Bamboo shoot production in Indonesia is also very abundant. The purpose of this activity is to increase the creativity of PGSD students as an effort to form an entrepreneurial spirit by making bamboo shoot chips. This service utilizes bamboo shoots into processed food ingredients that are rich in water, fiber, potassium, protein, fat and carbohydrates in the form of bamboo shoot chips. This activity trains students to make observations, environmental research, and also market research to find out about the availability of raw materials and analyze market share. This activity also trains students to carry out the pre-production, production, packaging, online and offline marketing stages as well as evaluation of the products produced. The result of this activity is the growth of an entrepreneurial spirit in PGSD students by making works in the form of bamboo shoot chips. Student creativity is reflected in the many flavors as an innovation to make bamboo shoot chips more attractive. The flavors that were innovated by PGSD students were balado, cheese, roasted corn, extra spicy and original.